NILAI PENDIDIKAN KARAKTER DALAM GAGURITAN PUYUNG SUGIH - Putu Subawa (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2018)
Character education is a system that instills character values ??in students, which involvesa component of knowledge, individual awareness, determination, and also the willingness andaction of the values, both to God Almighty, self, human sesame, environment, or nation, watuwill be realized by the human being (Aunillah, 2011: 18-19). The main foundation that must beused as a basis for implementing education is universal morality that can be extracted fromreligion, in this case the teachings available in the Vedas or the Holy Scriptures of Hinduism,especially in the lontar, kekawin-kekawin, geguritan-geguritan in Bali, therefore the values??derived from this holy book are the most appropriate way for everyone. Of the many existinggeguritan, the focus of this research is Geguritan Puyung Sugih. Geguritan Puyung Sugih arealso many people who use Hinduism education as well as general education values. The manyvalues ??contained in this Puyung Sugih geguritan post a strong appeal to be studied in order tobe used in life.